Intraoperative intraocular pressure fluctuation during standard phacoemulsification in real human patients - Hejsek, Libor; Kadlecova, Jana; Sin, Martin; Velika, Vera; Jiraskova, Nada (Biomedical papers, 2019)
Introduction: To evaluate the results of the fluctuations of intraocular pressure (IOP) and calculated mean ocular perfusion pressure (MOPP) during the usual steps of standard phacoemulsification. Methods: Nine human eyes were evaluated. The IOP was measured indirectly by electronic applanation tonometer. The MOPP was calculated using the systolic blood pressure (SBP), the diastolic blood pressure (DBP) and the IOP: MOPP = 2/3x[DBP + 1/3x(SBP - DBP)] - IOP. The operations were performed with the INFINITI(R) Vision System: main incision 2.2 mm, coaxial handpiece, 2 paracenteses 1.1 mm, bimanual irrigation/aspiration, bottle height 100 cm. As ocular viscoelastic device (OVD) Hypromel 2.5% (UNIMED) was used. Results: The initial and final IOPs were 17-30 Torr (median 18) and 6-16 Torr (median 8), respectively. The IOP values oscillated between 4 and 63 Torr during the procedure. The highest values of the IOP were achieved at the beginning of phacoemulsification (from 42 to 63 Torr). The maximum pressure higher than 50 mmHg and 60 mmHg was found in 89% and 30% of cases, respectively. The mean ocular perfusion pressure (MOPP) at the beginning of the procedure was 46.4-67.0 (median 53.3) and 0.4-42.0 (median 19.3) during the maximum intraocular pressure. Conclusions: Measured IOP as well as MOPP varied in all normal steps of real phacoemulsification. High values of intraoperative IOL induced by irrigation may compromise the intraocular perfusion. These fluctuations may induce impairment of the optic nerve perfusion, as well as retina, or choroid.
Keywords: intraocular pressure; intraoperative IOP; phacoemulsification; perfusion